Nurses Finding the Voice: Nursing Advocacy Roles and Lessons from the Pandemic - Valdez, Glenn Ford; Torres , Gian Carlo (Iraqi National Journal of Nursing Specialties, 2023)
Modern healthcare is built on nursing advocacy, and nurses perform crucial roles as advocates in many different contexts. This brief communication paper examines the varied nature of nursing advocacy and its importance in the provision of healthcare. Nurses are primary caregivers and in a unique position to uphold patients’ rights and needs while promoting patient-centered care. To ensure that patients’ voices are heard and appreciated, they act as communicators, bridging gaps between patients and healthcare teams. To sum up, nurses play an advocacy role that is revolutionary for the healthcare system as well as vital. Not only have nurses found their voices, but they have also used them to advocate for changes in the healthcare system and to fight for the rights and welfare of patients.